Transformation of African Agrifood Systems in the New Era of Rapid Urbanization and the Emergence of a Middle Class - Reardon, Thomas; Tschirley, David; Minten, Bart; Haggblade, Steven; Liverpool-Tasie, Lenis Saweda O.; Dolislager, Michael; Snyder, Jason; Ilumba, Claire (International Food Policy Research Institute, 2015)
This paper first looks “downstream” at two processes—urbanization and dietary changes—that create the demand (“pull”) for the changes in the whole food system. It then provides some illustrations of the transformation, mainly at the “midstream,” post-farmgate segments of the supply chains that are transforming—wholesale, processing, and logistics. It concludes with the implications of this transformation.